2016
DOI: 10.1152/jn.00255.2015
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal spatial working memory network predicts animal's decision making in a free choice saccade task

Abstract: While neurons in the lateral prefrontal cortex (PFC) encode spatial information during the performance of working memory tasks, they are also known to participate in subjective behavior such as spatial attention and action selection. In the present study, we analyzed the activity of primate PFC neurons during the performance of a free choice memory-guided saccade task in which the monkeys needed to choose a saccade direction by themselves. In trials when the receptive field location was subsequently chosen by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 72 publications
2
22
0
Order By: Relevance
“…Importantly the decision neurons’ activity could not depend on differences in visual responses because all three targets were always presented. Thus, our results indicate that neurons that exhibit a bias in the prestimulus period are not necessarily dissociated from those that are involved in decision formation, as proposed (Maoz et al, 2013 ), and that a neural response bias can emerge, even in the absence of a value-based decision in line with the results of Mochizuki and Funahashi ( 2016 ). In our free-choice condition, decision and motor neurons anticipated the choice long before the stimulus was presented and held it until the onset of movement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly the decision neurons’ activity could not depend on differences in visual responses because all three targets were always presented. Thus, our results indicate that neurons that exhibit a bias in the prestimulus period are not necessarily dissociated from those that are involved in decision formation, as proposed (Maoz et al, 2013 ), and that a neural response bias can emerge, even in the absence of a value-based decision in line with the results of Mochizuki and Funahashi ( 2016 ). In our free-choice condition, decision and motor neurons anticipated the choice long before the stimulus was presented and held it until the onset of movement.…”
Section: Discussionsupporting
confidence: 90%
“…One possible explanation for the absence of a neural bias in the PF in these experiments (Kim and Shadlen, 1999 ; Roy et al, 2014 ) is that they required a perceptual choice rather than a goal choice as in our task. In a recent study (Mochizuki and Funahashi, 2016 ), it was reported that the prestimulus activity of some neurons in PF was predictive of the future choice of monkeys. However, whether the neurons that exhibited the predictive power were those involved in decision or motor processes was not distinguished.…”
Section: Discussionmentioning
confidence: 99%
“…Planning an instructed saccade involves the same effector specific circuits that execute eye movements, namely, the frontal eye fields (FEFs) [2,3] and the lateral intraparietal area (LIP), [4][5][6][7][8], as well as a characteristic sustained neuronal activity in frontal areas, representing information about stimuli maintained in working memory during the delay period [9][10][11]. On the other hand, although monkey studies have demonstrated that free-choice decision processes (e.g., choosing between 2 equal reward options) appear to be represented in an effector specific frontoparietal network [12][13][14][15][16][17][18][19][20][21], the temporal dynamics of the neural correlates of free-choice decisions compared with those underlying instructed planning are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…It is also necessary to perform D1R manipulations in FEF and DLPFC while testing both for spatial WM performance and attentional selection of response goals. An interesting possibility would be to study dopamine modulation in a task that incorporates both WM and response selection between competing alternatives, like the free-choice saccade task recently explored by Mochizuki and Funahashi ( 2016 ), where PFC activity was found to predict the eventual free choice of a saccadic goal.…”
Section: Introductionmentioning
confidence: 99%